AB0003 GENETICS OF PAIN IN WOMEN WITH FIBROMYALGIA: THE PROMISING ROLE OF REDUCING SEDENTARY BEHAVIOUR. (June 2019) - Estevez-Lopez, Fernando; Salazar-Tortosa, Diego; Aparicio, Virginia A.; Camiletti-Moirón, Daniel; Carrera, Blanca Gavilán; Acosta-Manzano, Pedro; Alvarez-Gallardo, Inmaculada C.; Segura-Jiménez, Víctor; Maldonado, Alberto Soriano; Finan, Patrick; Geenen, Rinie; Delgado-Fernández, Manuel; et al.
Abstract : Background: Fibromyalgia is characterised by chronic pain and a heterogeneous presentation of other symptoms (e.g., fatigue and depression) [1]. It is widely accepted that pain is promoted by both genetic susceptibility and environmental factors such as people's behaviours [2]. In addition to genotype individual associations and gene-gene interactions, when considering complex phenotypes such as pain, gene-environmental interactions are likely present and can help to better understand the disease (i.e. by unravelling underlying mechanisms [3]). Objectives: To test the individual association of 64 polymorphisms (34 candidate-genes) and the gene-gene, gene-physical activity, and gene-sedentary behaviour interactions with pain and pain-related cognitions in fibromyalgia. Methods: In 274 women with fibromyalgia, saliva samples were collected for extracting DNA. We measured physical activity and sedentary behaviour by accelerometers for a week, pain with algometry and questionnaires, and pain cognitions with questionnaires. Age, body fat, and analgesics and antidepressants consumption were included as covariates. Significance was set at P-values lower than the Bonferroni's correction or P- and false discovery rate values lower than 0.05. Results: The rs6311 and rs6313 polymorphisms were individually related to algometer scores. The interaction of rs4818 and rs1799971 polymorphisms was related to pain catastrophizing. Five gene-behaviour interactions were significant: the interactions of sedentary behaviour with rs1383914, rs6860, rs4680, rs165599, and rs12994338 polymorphisms were associated with the bodily pain subscale of the SF-36. Conclusion: The HTR2A gene (individually), COMT and OPRM1 gene-gene interaction, and the interactions of sedentary behaviour with ADRA1A, CHMP1A, COMT, and SCN9A genes were associated with pain-related outcomes in fibromyalgia females. Besides indicating the relevance of genetic background for pain and pain-catastrophizing, the observed genotype-behaviour interactions suggest that the effects of sedentary behaviour on pain may depend on the genotype of women with fibromyalgia. Future clinical experimental research should examine whether reducing sedentary behaviour is particularly beneficial for reducing pain in women with specific genotypes. References: [1] Estévez-López F, et al. Rheumatology (Oxford). 2017Nov;56(11):2015-2024 [2] Nielsen CS, et al. Pain. 2008May;136(1-2):21-9 [3] Hunter DJ. Nat Rev Genet. 2005Apr;6(4):287-98 Acknowledgement: This work was supported by the Spanish Ministry of Economy and Competitiveness [I+D+i DEP2010-15639, I+D+i DEP2013-40908-R to M.D.-F.; BES-2014-067612 to F.E.-L.], the Spanish Ministry of Education [FPU13/03410 to D.S.-T.; FPU15/0002 to B.G.-C.], the Consejería de Turismo, Comercio y Deporte, Junta de Andalucía [CTCD-201000019242-TRA to MD-F], the Consejería de Salud, Junta de Andalucía [PI-0520-2016 to M.D.-F.], and the University of Granada, Plan Propio de Investigación 2016, Excellence actions: Units of Excellence; Unit of Excellence on Exercise and Health (UCEES). Disclosure of Interests: None declared